Varietal Assessment, Correlation Studies and Path Coefficient Analysis in Apple in High Hill Conditions of Himachal Pradesh, India - Thakur, P.; Chauhan, N.; Thakur, D. S.; Verma, P.; Thakur, M. (International Journal of Bio-resource and Stress Management, 2025)
The present investigation was conducted during March, 2023-October, 2024 at Regional Horticultural Research and Training Station Mashobra, Shimla, Himachal Pradesh, India to assess varietal diversity and inter-relationships between the various traits in 30 apple cultivars. Data was collected for physical and biochemical characters of fruits. Maximum fruit weight (184.62 g), length (7.00 cm) and breadth (7.47 cm) was recorded in variety Red Delicious, while highest fruit firmness was found in Carrol (9.15 kg cm-2). Regarding biochemical analysis highest TSS (14.77°Brix) and juice content (87.52%) was recorded in variety Honey Gold and maximum acidity (0.75%) was present in Granny Smith. Maximum ascorbic acid was found in Scarlet Spur II (6.55 mg 100 g-1) and anthocyanin content was recorded in variety King Roat (16.89 mg 100 g-1). Estimating correlations and path analysis between variables is widely used to determine how to enhance important attributes for crop quality. Fruit weight was found to be positively and significantly associated with fruit length (0.609), breadth (0.742), titratable acidity (0.255) and juice content (0.458). Path coefficient analysis revealed that various traits such as fruit length (0.504), breadth (0.304), firmness (0.013), acidity (0.199) and juice content (0.197) had positive direct effects on fruit weight, however direct negative effect on fruit weight was recorded with TSS (-0.316), ascorbic acid (-0.202) and anthocyanin content (-0.076). It was thus concluded that these physico-chemical traits used as selection indicators for increased production with high-quality apple cultivars.